Public perception of xenotransplantation and its implication for policy and regulation: lessons learnt from a qualitative study of the Swedish public - Rui Liu; Markus Idvall; Susanne Lundin (Transplant International, 2026)
The field of xenotransplantation is advances rapidly. Its cross-species nature creates regulatory challenges different from those in allotransplantation. Public opinion is promoted as an essential element in developing responsible governance for this technology. This study takes a qualitative thematic approach to analyze data collected through a questionnaire (n = 136) to the Swedish public. The aim is, first, to analyze how respondents articulate concerns, hopes, and moral evaluations regarding XT, and second, to reflect on what these responses reveal about the methodological conditions required for meaningful public engagement in the development of regulatory frameworks for emerging biomedical technologies. The findings demonstrate that public views are not directly associated with the technical assessment of risk and benefit but are anchored in shifting sociocultural perceptions regarding human survival, animal welfare, and vulnerability as individuals move between different scenarios. We conclude that developing policy and regulations for XT require continuous engagement with the underlying public opinions. We learned that meaningful public engagement with emerging biomedical technologies involves sustained processes of familiarization, communication, and dialogue between science, society, and policy.